THE INFLUENCE OF ENTREPRENEURIAL CHARACTERISTICS, ENTREPRENEURIAL COMPETENCE, AND BUSINESS LOCATION ON BUSINESS SUCCESS - Rahmawati, Desi; Lona Chinsia Alfattama; Angel Zeiromardalina Ghahar (Universitas Tulungagung, 2024)
This research is motivated by the importance of entrepreneurship in overcoming Indonesia's high unemployment rate. Success in building a successful economy also depends heavily on the characteristics and competencies of each entrepreneur. The purpose of this study was to determine whether there is an influence between entrepreneurial characteristics, entrepreneurial competencies, and business location on business success in the Marble Craft Industry of Gamping Village, Campurdarat District, Tulungagung Regency, both partially and simultaneously. The research method used is Quantitative with the type of Explanatory Research. The sampling technique uses Probability Sampling with a sample size of 75 Marble Craft Industry entrepreneurs, and data processing uses the SPSS version 27 program. The study results indicate that partially entrepreneurial characteristics and competencies have a significant positive effect. In contrast, business location significantly negatively affects business success in the Marble Craft Industry of Gamping Village, Campurdarat District, Tulungagung Regency. Simultaneously, entrepreneurial characteristics, entrepreneurial competencies, and business location have a significant effect together (simultaneously) on business success in the Marble Craft Industry of Camping Village, Campurdarat District, Tulungagung Regency.